The relative accuracy of 4D dose accumulation for lung radiotherapy using rigid dose projection versus dose recalculation on every breathing phase. Issue 3 (17th March 2017) - Valdes, Gilmer; Lee, Chul; Tenn, Stephen; Lee, Percy; Robinson, Clifford; Iwamoto, Keisuke; Low, Daniel; Lamb, James M.
Abstract : Purpose: To investigate the accuracy of 4D dose accumulation using projection of dose calculated on the end‐exhalation, mid‐ventilation, or average intensity breathing phase CT scan, versus dose accumulation performed using full Monte Carlo dose recalculation on every breathing phase. Methods: Radiotherapy plans for 10 patients with stage I–II lung cancer were analyzed. All patients had respiratory‐correlated computed tomography (4D‐CT) performed as part of an IRB‐approved research protocol. Stereotactic body radiotherapy (SBRT) plans were optimized using the dose calculated by a commercially available Monte Carlo algorithm on the end‐exhalation 4D‐CT phase. 4D dose accumulations using deformable registration were performed with a commercially available tool that projected the planned dose onto every breathing phase without recalculation, as well as with a Monte Carlo recalculation of the dose on all breathing phases. The 3D planned dose (3D‐EX), the 3D dose calculated on the average intensity image (3D‐AVE), and the 4D accumulations of the dose calculated on the end‐exhalation phase CT (4D‐PR‐EX), the mid‐ventilation phase CT (4D‐PR‐MID), and the average intensity image (4D‐PR‐AVE), respectively, were compared against the accumulation of the Monte Carlo dose recalculated on every phase. Plan evaluation metrics relating to target volumes and critical structures relevant for lung SBRT were analyzed. Results: Plan evaluation metrics tabulated using 4D‐PR‐EX, 4D‐PR‐MID, and 4D‐PR‐AVE differed from those tabulated using Monte Carlo recalculation on every phase by an average of 0.14 ± 0.70 Gy, −0.11 ± 0.51 Gy, and 0.00 ± 0.62 Gy, respectively. Plan evaluation metrics calculated from 3D‐EX and 3D‐AVE were acceptably accurate for target volumes and most critical structures, however, deviations of between 8 and 13 Gy were observed for the proximal bronchial trees of three patients. Conclusions: The accuracy of 4D dose accumulated by projecting the dose calculated on the end‐exhale, mid‐ventilation, and average intensity images has been presented for 10 lung cancer SRBT plans. These methods involving projection without recalculation may be sufficiently accurate compared to 4D dose accumulated from Monte Carlo recalculation on every phase, depending on institutional protocols. Projection of the dose calculated on the mid‐ventilation scan was found to be statistically significantly more accurate than projection of the dose calculated on end‐exhalation when considering target volume dose metrics. Use of 4D dose accumulation should be considered when evaluating normal tissue complication probabilities as well as in clinical situations where target volumes are directly inferior to mobile critical structures.